The Clinical Effects of Intravascular Ultrasound-Guided Percutaneous Coronary Intervention in Patients with Chronic Total Occlusion: A Meta-Analysis - Zhaoshuang Zhong; Long Zhao; Kaiming Chen; Shuyue Xia (Cardiology Research and Practice)
Background. The clinical effects of intravascular ultrasound (IVUS)-guided percutaneous coronary intervention (PCI) in patients with chronic total occlusion (CTO) lesions remain unclear. Methods. We identified all full-text published studies that compared the effects of IVUS-guided CTO-PCI with angiography-guided CTO-PCI by searching electric databases including PubMed, Embase, Cochrane Library, and ISI Web of Science from the establishment to Nov 2021. There was no language limitation. The endpoints included the incidence of major adverse cardiac events (MACE), cardiac death, all-cause death, myocardial infarction (MI), and target vessel revascularization (TVR). Results. Five studies involving a total of 2320 patients were included in this meta-analysis. Compared to the angiography-guided group, IVUS-guided PCI showed no significant reduction in the incidence of MACE (I2 = 27.4%, P = 0.239; RR 0.929, 95% CI 0.765 to 1.128, P = 0.457), cardiac death (I2 = 0.0%, P = 0.459; RR 0.574, 95% CI 0.299 to 1.103, P = 0.096), all-cause death (I2 = 0.0%, P = 0.964; RR 0.677, 95% CI 0.395 to 1.163, P = 0.158), MI (I2 = 46.7%, P = 0.131; RR0.836, 95% CI 0.508 to 1.377, P = 0.482), and TVR (I2 = 21.2%, P = 0.279; RR 0.929, 95% CI 0.679 to 1.272, P = 0.648). Conclusions. IVUS-guided PCI demonstrated no significant benefit on MACE, cardiac death, all-cause death, MI, and TVR in patients with CTO lesions. However, given the study’s limitations, additional high-quality RCTs are needed.